2011
DOI: 10.1253/circj.cj-10-0736
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variants of Coronary Venous System on Cardiac Computed Tomography

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp he variety of cardiac devices for transvenous implantation has increased in the years, mostly due to evidence of effectiveness of this therapy in chronic heart failure. Special attention is placed on cardiac resynchronization therapy (CRT) or combination of those devices with implanted cardioverter defibrillator. 1-5 During these procedures, the implantation of left ventricle lead is necessary. The only way for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 28 publications
3
19
0
5
Order By: Relevance
“…In 2011 we described the anatomical variants of the coronary venous system [19]. In this research we confirmed a high degree of anatomical variability in the cardiac vein -this was also corroborated by Malagò et al [17] and Chan et al [15].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In 2011 we described the anatomical variants of the coronary venous system [19]. In this research we confirmed a high degree of anatomical variability in the cardiac vein -this was also corroborated by Malagò et al [17] and Chan et al [15].…”
Section: Discussionsupporting
confidence: 82%
“…There are some imaging techniques that can visualise the anatomy of the coronary venous system in live subjects [15]. Multi-slice computed tomography (MSCT) appears to be the most accurate and is probably the most frequently used imaging technique for venous anatomy evaluation [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…There are several types of coronary venous system imaging, each of which has its own advantages and disadvantages (12,(20)(21)(22)(23). The conventional method used to evaluate coronary venous system is invasive retrograde cardiac venography.…”
Section: Discussionmentioning
confidence: 99%
“…In all of the patients, the coronary venous system was analyzed including the number of visible coronary veins and the type of veins visualized (coronary sinus, anterior, antero-lateral, lateral, postero-lateral, posterior veins and middle cardiac veins). The nomenclature of those vessels was based on earlier published methodology [8]. …”
Section: Methodsmentioning
confidence: 99%